Effectiveness of Legal Protection Regarding Workers' Wage Rights in The Micro, Small and Medium Enterprise Sector - Rachmawati, Meida (International Journal of Law Social Sciences and Management, 2025)
Abstract. This study discusses wage protection in the employment system in Indonesia, with a focus on the Micro, Small, and Medium Enterprises (MSMEs) sector, as well as the challenges faced in implementing wage regulations, such as Government Regulation Number 36 of 2021 concerning Wages and Government Regulation Number 51 of 2023 concerning Amendments to Government Regulation Number 36 of 2021 concerning Wages. This study examines the extent to of salary policies can maintain workers' welfare without burdening MSME entrepreneurs. The research method used is normative juridical with a statute approach and a conceptual approach, which allows for an in-depth analysis of related regulations and their implications for the implementation of minimum wages in the MSME sector. The results of the study show that although regulations already exist, implementation is still hampered by low legal awareness, weak supervision, and inequality in wage negotiations between employers and workers, which impact the uncertainty of protecting workers' rights.